Testicular sperm results in elevated miscarriage rates compared to epididymal sperm in azoospermic patients - Borges Júnior,Edson (2002)
CONTEXT: Several sperm retrievel techniques are available for use on azoospeermic men. Comparisons between spermatozoa retrieved from the testicles and epidymis in relation to pregnancy and miscarriage rates are not well established. OBJECTIVE: To compare pregnancy and miscarriage rates using sperm retrieved from the testes and epididymis using intracytoplasmic sperm injection. Furthermore, we evaluated the fertilization and pregnancy rates according to the status of the spermatozoa retrieved (motile or immotile). DESIGN: Retrospective study. SETTING: A private center for assisted fertilization. PARTICIPANTS: One hundred and eight consecutive patients who presented with azoospermia were included in our study, on whom a total of 144 retrieval procedures were performed. PROCEDURES: Of the 144 retrieval procedures, 104 were testicular sperm aspirations (TESA) and 40 were epididymal sperm aspirations (PESA). PESA was the first approach in obstructive patients (n = 68), whereas TESA was used when the former failed. For non-obstructive patients (n = 40), TESA was the method of retrieval. MAIN MEASUREMENTS: Pregnancy and miscarriage rates according to spermatozoa characteristics (motile or immotile). RESULTS: The number of cycles performed using spermatozoa retrieved from the testicles and epididymis was 81 and 30, respectively. Motile spermatozoa had higher fertilization (2PN) and pregnancy rates compared to immotile spermatozoa (p < 0.05). Also, motile spermatozoa had lower miscarriage rates compared to immotile spermatozoa (p < 0.0001). No differences were seen in pregnancy rates with testicular spermatozoa (n = 28) compared to epididymal spermatozoa (n = 13) (p = 0.1). However, the miscarriages rates were higher in spermatozoa retrieved from the testicles (n = 12) compared to epididymis retrievals (n = 1) (p = 0.01). CONCLUSIONS: Although pregnancy rates were similar when the intracytoplasmic sperm injection was performed with spermatozoa retrieved from the testicles and epididymis, the use of testicular spermatozoa yields a significantly higher miscarriage rate. It is possible that the higher miscarriage rate seen in patients using spermatozoa retrieved from the testicles is linked to high genetic sperm abnormalities.